Alagwa - Agatep, Pia Augustha G. 1985-
"Our film centers on the likeness of twins, on how they are connected despite their physical distance from one another and the struggle of an individual for the realization of true self. It is difficult to establish and physically show the special connection twins share, an invisible bond that only they can identify and understand. The realization of the true self is a goal every individual has. Individuation is the process that we go through to attain totality. The realization of one's uniqueness tapping into the self is essential to again keep in touch with ourselves. This is the main goal of the protagonist of the film: to achieve excellence in her talent and to discover her own abilities."